PENGARUH KEDALAMAN MUKA AIR TANAH DAN MULSA ORGANIK TERHADAP SIFAT FISIK DAN KIMIA TANAH GAMBUT PADA PERKEBUNAN KELAPA SAWIT (Elaeis guineensis.Jacq) - Petrus Candranius Situmorang; Wawan '; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This researh aimed to determine the effect of water level and organic mulch on physical and chemical properties of peatland in palm oil plantation. Research was conducted for four months which is started on November 2014 to February 2015 at palm oil plantation of ​​PT. Teguh Karsa Wana Lestari (TKWL) in Buantan Besar village, sub district Bungaraya, Siak District. By used 8 years old of palm oil plant. This research used Split Plot Design, consist of 2 factors. The first factor is the water level as main plot, were: the level of 40-50 cm water, 60-70 cm water level and 80-90 cm water level. The second factor is giving organic mulch as sub plot, were: without giving organic mulch, giving palm oil empty fruit bunch (POEFB), palm frond and Mucuna Bracteata. Therefore obtained 12 combinations of treatments and 3 replications, so obtained 36 units experiment. Parameters observed were physical and chemical properties. Data were analyzed by Analysis of Variance (ANOVA) and were further tested by Least Significant Diference (LSD) at5 % level. Based on statistical data obtained non significant effects by water level and organic mulch in physical and chemical properties of peatland. The result of single factor by organic mulch obtained significant effects in physical and chemical properties of peatland. The result of single factor by water level obtained significant effects in peatland water content parameters. Keywords : Physical and chemical properties, water level, organic mulch in peatland